Caracterização de Pitcairnia flammea (Bromeliaceae), ocorrente em fragmentos de Mata Atlântica, por meio de ferramentas biotecnológicas - Nogueira, Ester Ujiie (2010)
RAPD molecular markers are useful for analyzing genetic diversity, enabling a broader sampling of unknown genomes. SSR and ISSR markers are also used for this purpose, but still only a few are developed to Bromeliaceae, which implies the validation of the